PENGUASAAN TERHADAP RUMAH APUNG YANG DITANAM DI PERAIRAN DITINJAU DENGAN OBJEK PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN MENURUT UNDANG - UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Sylvie Liunadi; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
The existence of floating houses in Indonesia has existed since the Dutch colonial era. Floating houses are scattered in several provinces in Indonesia, such as in Sulawesi, Kalimantan and Palembang. This floating house stands with a construction system planted on water land controlled by the state. Article 1 Paragraph (39) of the Regional Tax and Retribution Law defines a building, not only a building that stands on land in general, but also a building that can stand on water. Every control when the object is embedded in the earth or the surface of the land, it is clear that someone who controls the object embedded in the earth, so that the floating house that is embedded in the water does not belong to the people anymore, therefore the floating house which is embedded in the land of waters clearly controls and the person must pay taxes or be taxed by law. In this study the authors used a normative legal research method, with a statutory approach, by examining library materials (literature study). Legal materials used in this research are primary legal materials, secondary legal materials and non-legal materials. From the research that has been done, it can be concluded that the definition of a floating house is the object of Rural and Urban Land and Building Tax because it is attached to the earth so that the land and / or buildings that have been controlled, owned and / or used by private persons.